Monetary policy and economic development in India - Patnaik, Khetra Mohan (Delhi : S. Chand & Co., 1966)
This book is concerned with an analysis of compatibility of monetary policy of the Reserve Bank of India during the First and second five year plan period with what is appropriate in the context of development
Thesis - Utkal University.
Includes bibliographical references: p. [277] - 281.
gp. 24/01/2019
Loan
Keywords: Monetary policy